Introduction to robotics : analysis, control, applications - Niku, Saeed B. (Saeed Benjamin) (Hoboken, N.J : Wiley, 2011)
"Niku offers comprehensive, yet concise coverage of robotics that will appeal to engineers. Robotic applications are drawn from a wide variety of fields. Emphasis is placed on design along with analysis and modeling. Kinematics and dynamics are covered extensively in an accessible style. Vision systems are discussed in detail, which is a cutting-edge area in robotics. Engineers will also find a running design project that reinforces the concepts by having them apply what they've learned."--
Includes bibliographical references and index.
Keywords: Robotics